Performance of modified asphalt mixes by replacing crumb rubber as fine aggregates - Syafiqa Areesa, Zamri (2017)
Malaysia has the shortage of the natural resource and there are so many other reusable and recycle thing that could possibly substituting the natural resources as alternatives. Researchers have been looking and studying the ways to reduce the usage of the natural resources and encounter the problem. The wastes tires from road transportation have high potential to be recycled and reused as aggregates. The waste tires are been processed by grinding and separating the materials. The crumb rubber is collected from the waste tires. Nevertheless, due to the fact that rubber employed in tire fabrication is the result of specialized materials’ selection, recycling and reuse seem to be preferable options for such a high-quality waste material. The pavement in Malaysia still using the conventional method of Marshall mix design and tested by the physical properties for the Marshall Stability test. This study to improve and enhance the pavement quality by using crumb rubber as the fine aggregates in the hot mix asphalt by using the conventional method of Marshall Mix design. The crumb rubber is used by percentages of1%, 2% and 3% of the weight of the fine aggregate used in the original mix design. The usage of the crumb rubber was by using the dry process. The crumb rubber is mixed as fine aggregates in the mix with constant binder of 4%, 5% and 6% respectively. The Marshall method uses standard test samples of 64mm thickness x 100mm diameter. The samples then were tested for indirect tensile test by using the MATTA machine UTM-25. The samples were tested for the resilient modulus, horizontal and the peak loading forces. The original samples with 0% or the usage of crumb rubber are act the control samples which were compared to the other samples with the usage of the crumb rubber of 1%, 2% and 3%. The results are tabulated and presented in graphs. The results exhibit that the quality of the pavement with the usage of the crumb rubber can achieve the same quality of the original pavement mixes. The usage of crumb rubber with 2% shows optimum result for binder content of 4%, 5% and 6%. The contributions and the optimum crumb rubber is determined for all the binder content which in result shows the most closest quality achievement by the modified asphalt mixes with the existence of crumb rubber and the control sample.